Effects of food price spikes on household welfare in Nigeria - Adebayo Musediku Shittu; Dare Akerele; Mekbib Gebretsadik Haile (University of Bonn, Center for Development Research (ZEF), 2018)
The dramatic global food price upsurges of 2007/2008 and the resurgence of 2010/2011 have kept the welfare effects of food price shocks at the epicentre of policy discussions worldwide. Studies have found heterogeneous impacts, but empirically little is known in Nigeria. The key objectives of this study are to examine the welfare, i.e. food quantity consumption, dietary diversity, and economic welfare effects of food price spikes among households in Nigeria. Using the 2012/2013 and 2015/2016 Household Survey Panel Data, the linear individual (fixed) effects models were estimated while controlling for participation in safety net interventions and other factors to achieve the stated objectives. Findings suggest that higher spike in the price of cereals consistently has negative effect on food quantity (including calories) consumed, dietary diversity, and economic welfare of households, spikes of price of other staples, animal proteins, fats and oils, fruits and vegetables exert heterogeneous influence. Female headed households advance calorie consumption and dietary variety. Findings suggest that food distribution may be more effective in improving welfare of households than direct cash transfers. Efforts to mitigate extreme spikes in the prices of staples (especially cereals) are relevant for improved food security, nutrition and overall household welfare. However, if policy actions are complemented with food distribution and sensitively guided welfare related gender interventions, more improvements for livelihoods can be achieved.
Keywords: 330; Price Shocks; Food Security; Economic Welfare; Safety Nets; Nigeria